2003
DOI: 10.1007/s00442-003-1439-5
|View full text |Cite
|
Sign up to set email alerts
|

Minimum recruitment frequency in plants with episodic recruitment

Abstract: There is concern about the lack of recruitment of Acacia trees in the Negev desert of Israel. We have developed three models to estimate the frequency of recruitment necessary for long-term population survival (i.e. positive average population growth for 1,000 years and < 10% probability of extinction). Two models assume purely episodic recruitment based on the general notion that recruitment in arid environments is highly episodic. They differ in that the deterministic model investigates average dynamics whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 29 publications
1
55
0
Order By: Relevance
“…Successful recruitment seems to require several consecutive rainfall events (unpublished ACACIA interview data; Wiegand et al 2004). The fact that 4 of 5 trees at Nuqrus were established in a limited period might be due to how the sampled trees were selected, but might just as well indicate that the Nuqrus catchment had received more frequent rains during the time of establishment than later.…”
Section: Discussionmentioning
confidence: 99%
“…Successful recruitment seems to require several consecutive rainfall events (unpublished ACACIA interview data; Wiegand et al 2004). The fact that 4 of 5 trees at Nuqrus were established in a limited period might be due to how the sampled trees were selected, but might just as well indicate that the Nuqrus catchment had received more frequent rains during the time of establishment than later.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in rates of tree establishment, whether due to fire (Higgins et al 2000), herbivory (Dublin et al 1990, Prins and van der Jeugd 1993, Baxter and Getz 2005 or climate variability (Watson et al 1997, Wiegand et al 1999, Wiegand et al 2004, may indeed play a major role in shaping the long-term, apparently stable, coexistence of trees and grasses. Spatial patchiness in establishment, at both the stand and hillside level, suggests that landscape processes such as fire and herbivory impact strongly on rates of tree establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical work has argued that variability in establishment rates of adult savanna trees is fundamental to promoting the coexistence of grasses (Higgins et al 2000). Modeling work has also shown that variability in climate, herbivory and fire can produce variability in tree establishment that tracks broad-scale patterns in ecosystem change (Dublin et al 1990, Watson et al 1997, Woodward and Beerling 1997, Wiegand et al 1999, Higgins et al 2000, Wiegand et al 2004, Baxter and Getz 2005. However, empirical work evaluating whether variability in savanna tree establishment actually occurs and investigating the types of demographic variability that characterize savanna tree populations is rare.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Negev desert, for example, suitable conditions for germination occur every 3-4 years (Ashkenazi 1995). According to a semi-stochastic model, approximately two mast events of highly successful recruitment per century combined with a low annual probability of recruitment events are necessary to sustain A. raddiana populations in the Negev desert (Wiegand et al 2004). Maximum adult survival is about 50 years .…”
Section: Study Systemmentioning
confidence: 99%